An Elephant Herding Optimization Approach to Enhance the Performance of SEIG in Transient and Steady State - Gurdiyal Singh, Prof. V. R. Singh (International Journal of Advanced Science and Technology, 2020)
An Elephant Herding Optimization (EHO) is presented to enhance the performance of single phase Self Excited Induction Generator (SEIG) in steady and transient state. The parameters of single phase SEIG such as speed, frequency, impedance, total harmonic distortion and terminal voltage are optimized using proposed approach. The results are compared with Particle Swarm Optimization (PSO) and Firefly method (FM) using MATLAB. The results are more effective than existing approach.